2012
DOI: 10.1039/c2jm33980c
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-sensitive mesoporous N-doped Ta2O5 spheres: synthesis and photocatalytic activity for hydrogen evolution and CO2 reduction

Abstract: Crystallized mesoporous tantalum pentoxide spheres (CMTS) with particle diameters of ca. 100-500 nm and composed of Ta 2 O 5 nanocrystals were synthesized for the first time by a combination of the sol-gel process and heat-treatment with the aid of carbon reinforcement. The specific surface area of the CMTS was up to 105 m 2 g À1 and the pore diameter was controllable in the range of 5.6-17 nm by changing the crystallization temperature. Visible light-sensitive p-type N-doped Ta 2 O 5 (N-CMTS) containing 5 at%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…It was believed that the mesoporous structure and N-doping were responsible for inhibiting the recombination of photogenerated electrons and holes and improving visible light absorption, respectively, thus leading to an improved photoactivity. The mesoporous nitrogen doped Ta 2 O 5 exhibits excellent photocatalytic activity for hydrogen evolution and CO 2 reduction (modified with ruthenium-complex) under visible-light irradiation due to their larger surface area, enhanced visible light absorption and controlled morphology [128]. Similar results were observed for nitrogen-doped InTaO 4 photocatalysts, which showed a 2-fold increase in the yield of methanol compared to the undoped one [124].…”
Section: Impurity Dopingsupporting
confidence: 75%
“…It was believed that the mesoporous structure and N-doping were responsible for inhibiting the recombination of photogenerated electrons and holes and improving visible light absorption, respectively, thus leading to an improved photoactivity. The mesoporous nitrogen doped Ta 2 O 5 exhibits excellent photocatalytic activity for hydrogen evolution and CO 2 reduction (modified with ruthenium-complex) under visible-light irradiation due to their larger surface area, enhanced visible light absorption and controlled morphology [128]. Similar results were observed for nitrogen-doped InTaO 4 photocatalysts, which showed a 2-fold increase in the yield of methanol compared to the undoped one [124].…”
Section: Impurity Dopingsupporting
confidence: 75%
“…[57]. In addition, Suzuki's group has obtained visible light-sensitive p-type N-doped Ta 2 O 5 spheres containing 5 at% N, which exhibits excellent photocatalytic activity for CO 2 reduction (with ruthenium-complex) under light irradiation (410 < < 750 nm) [56]. Liu and co-workers have prepared N-doped InTaO 4 modified with Ni@NiO core-shell nanostructure as cocatalyst, displaying photocatalytic reduction of CO 2 with H 2 O into CH 3 OH under light irradiation (390 < < 770 nm) [55].…”
Section: Cation or Anion Dopingmentioning
confidence: 98%
“…It is recognized to be more efficient for visible light harvesting than cation doping because of the fewer recombination centers formation compared to cation doping [49][50][51][52][53][54][55][56]. Specifically, Zhao et al have prepared N-doped TiO 2 nanotubes (N-TNTs) by hydrothermal method and it is found that because of the substitution of lattice oxygen by N atoms, N-doped TiO 2 shows efficient visible light absorption, and markedly improved visible light photocatalytic activities for CO 2 reduction to yield HCOOH, HCHO, CH 3 OH, etc.…”
Section: Cation or Anion Dopingmentioning
confidence: 99%
“…Due to the volume increase accompanying this reaction, self-induced crack healing will occur on the damaged surface [22]. Researchers have reported that TaOx are porous [23]. Moreover, has also been claimed that Ta 2 O 5 film, when less than 8 nm thick, has superior electron contributing properties [24].…”
Section: Introductionmentioning
confidence: 97%